Cellulase hydrolyzed Indigofera zolingeriana leaf utilization as a feed ingredient for gourami fingerling - Jefry, Jefry; Setiawati, Mia; Jusadi, Dedi; Fauzi, Ichsan Achmad (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
This study was aimed to evaluate the utilization of hydrolyzed Indigofera zolingeriana by celullase enzyme as the feed ingredient of gourami fish. This study used a completely randomized design which contained three steps, whereas each step contained four treatments and four replications. The first step performed by evaluating the Indigofera leaf meal (ILM) added with cellulase enzyme of 0 g/kg (control), 0.4 g/kg, 0.8 g/kg, and 1.2 g/kg. The second step was the digestibility test of ILM on gourami seeds. The third step was feed evaluation added with ILM as much as 0% (control), 15%, 30%, and 45% against the growth performance on gourami seeds. The gourami seeds used in the second and third steps with a weight of 13.65 ± 0.39 g/seed and 5.95 ± 0.15 g/seed, respectively. The addition of 0.8 g/kg and 1.2 g/kg cellulase enzyme could significantly decrease the crude fiber of ILM with 43.33%, besides having the best value of total, ingredient, protein, lipid, and energy digestibility. The growth performance of gourami seeds given 15% ILM added feed had the best value and insignificantly different from the control feed without ILM addition based on the specific growth rate (SGR), protein retention (PR), and feed efficiency (FE). Keywords: Cellulase, feed, hydrolyze, Indigofera zolingeriana, Osphronemus gouramy. ABSTRAK Penelitian ini dilakukan untuk mengevaluasi pemanfaatan daun Indigofera zolingeriana yang dihidrolisis enzim selulase sebagai bahan baku pada pakan benih ikan gurami. Penelitian ini menggunakan rancangan acak lengkap yang terdiri atas tiga tahap, dimana masing-masing tahap terdiri dari empat perlakuan dan empat ulangan. Pada tahap pertama dilakukan evaluasi tepung daun Indigofera (TDI) yang ditambahkan enzim selulase sebesar 0 g/kg (kontrol), 0.4 g/kg, 0.8 g/kg, dan 1.2 g/kg. Pada tahap kedua dilakukan uji kecernaan bahan TDI pada benih ikan gurami. Pada tahap ketiga dilakukan evaluasi pakan yang ditambahkan TDI sebesar 0% (kontrol), 15%, 30% dan 45% terhadap kinerja pertumbuhan pada benih ikan gurami. Benih ikan gurami yang digunakan pada penilitian tahap kedua dengan bobot 13.65 ± 0.39 g/ekor dan 5.95 ± 0.15 g/ekor. Penambahan enzim selulase pada dosis 0.8 g/kg dan 1.2 g/kg secara signifikan mampu menurunkan serat kasar TDI sebesar 43.33 % dan memberikan nilai terbaik terhadap nilai kecernaan total, kecernaan bahan, kecernaan protein, kecernaan lemak dan kecernaan energi. Kinerja pertumbuhan benih ikan gurami yang diberikan pakan yang ditambahkan TDI sebesar 15% memilki nilai terbaik dan tidak berbeda nyata terhadap pakan kontrol tanpa TDI dari aspek laju pertumbuhan spesifik (LPS), retensi protein (RP) dan efisiensi pakan (EP). Kata kunci: Hidrolisis, Indigofera zolingeriana, Osphronemus gouramy, pakan, selulase.